Genetic structure and diversity among three Greek sheep breeds using Random Amplified Polymorphic DNA-PCR - MASTRANESTASIS (Ι. ΜΑΣΤΡΑΝΕΣΤΑΣΗΣ), I.; LIGDA (Χρ. ΛΙΓΔΑ), Ch.; THEODOROU (Κ. ΘΕΟΔΩΡΟΥ), K.; EKATERINIADOU (Λ.Β. ΑΙΚΑΤΕΡΙΝΙΑΔΟΥ), L. V. (Journal of the Hellenic Veterinary Medical Society, 2017)
Genetic structure and diversity of 120 animals from three Greek local breeds were investigated by Random Amplified Polymorphic DNA (RAPD) - PCR method. Sheep samples originated from the Lesvos, Chios and Karagouniko breeds were treated with 11 random primers to estimate their genetic diversity and phylogenetic relationships. Our analysis comprised two levels of the breeds' genetic structure: i) the genetic differentiation among the three breeds and ii) the genetic differentiation among the flocks within each breed. This combined approach gave two main findings: i) the study of genetic distances and identity revealed that the Karagouniko sheep breed is genetically distinct from Chios (GD=0.1979) and Lesvos (GD=0.1691) breeds, while ii) the Chios and Lesvos breeds are genetically similar (GI=0.9631); half of the flocks of Lesvos have a relatively closer relationship with those of Chios than with the other Lesvos flocks. This is the first study that reports the close genetic relationship between the Chios and Lesvos breeds and gives strong evidence to hypotheses about their related origin. Furthermore, the study of polymorphic loci revealed particular indicators located in Karagouniko breed, as definitional datum of genetic identity or as a fingerprint of breed. Therefore, RAPD-DNA methods can be an efficient tool for the determination of phylogenetic relationships and genetic identity among the bloodstock breed of sheep.